Pengolahan dan Uji Kualitas Pupuk Organik Feses Sapi (Bos Taurus) dan Enceng Gondok (Eichhornia Crassipes) terhadap Pertambahan Tanaman - Nasihah, Mimatun; Istianah, A; Mujiati, Lilik (Universitas Islam Lamongan, 2019)
Usually, the people of Mojopetung Village, Dukun Subdistrict, Gresik Regency in disposing of waste from livestock are left idle in the ground if dried cow feces will be dumped into the rice fields. If in the rainy season the cattle fases will disappear by itself because it is carried by running water and the cow feces seep into will also flow into the river directly. This causes the water to not function properly and cause air and soil pollution. In addition, aquatic biota life is also disturbed not only because of cow feces (Bos taurus) but the existence of Eichhornia crassies which continue to increase people's habit does not use water as they should use as a place of animal baths.Â These problems can be overcome by processing cow feces with water hyacinth as compost. With the method of applying the fertilizer directly to plant. The method of data analysis was carried out using one-way ANOVA (Analysys of Variance) Test to find out whether or not the influence of organic fertilizer on plant growth.Â The results showed that the average height of the stem was 32.69 cm in the treatment using compost, 30.84 cm using urea fertilizer, 25.8 cm without fertilizer. The number of leaves that use compost, urea or no fertilizer results in an average value equal to 5 cm, and the leaf color produces a green average for each experiment. ANOVA test on plant growth results in F = 14.608> F table = 3.59. This shows that there are significant differences in plant growth in organic fertilizer applications. the number of leaves and the color of the leaves yielded F = 0 <F arithmetic = 3.59 and F = 0.2 <F arithmetic = 3.59 which showed no significant difference in the number of leaves and plant height.